Death by moderation the U.S. Military's quest for useable weapons - Koplow, David A. (Cambridge University Press, 2010)
This book addresses an important but little-noticed phenomenon in the revolutionary world of military technology. Across a wide range of otherwise-unrelated weapons programs, the Pentagon is now pursuing arms that are deliberately crafted to be less powerful, less deadly, and less destructive than the systems they are designed to supplement or replace.